2007
DOI: 10.1589/jpts.19.41
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Research Evidence for Selected Physical Therapy Interventions for Plantar Fasciitis

Abstract: To evaluate the strength of research evidence for selected interventions in the management of plantar fasciitis and compare the evidence with current clinical guidelines. A literature search of PubMed and CINAHL from 1995 to 2005 was conducted using articles that involve interventions that physical therapists would administer directly, are English-only, peer reviewed, prospective and retrospective studies, and whose interventions are supported at least two randomized controlled trials. Grouped by treatment cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Previous reviewers [11] and authors of clinical guidelines [1], included just two of the studies in this review [14, 15], and concluded that there is some, scientific evidence described as moderate quality [1], and poor quality [11] to support the use of stretching for the treatment of plantar heel pain in terms of short term relief. Landorf and Menz [4] included two primary studies in their review [15, 26] only one of which [15] fulfilled the inclusion criteria for this current review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reviewers [11] and authors of clinical guidelines [1], included just two of the studies in this review [14, 15], and concluded that there is some, scientific evidence described as moderate quality [1], and poor quality [11] to support the use of stretching for the treatment of plantar heel pain in terms of short term relief. Landorf and Menz [4] included two primary studies in their review [15, 26] only one of which [15] fulfilled the inclusion criteria for this current review.…”
Section: Discussionmentioning
confidence: 99%
“…The condition of Plantar Fasciitis is thought to arise from overuse or repetitive micro trauma of the tissue [9]. As the aetiology of plantar fasciitis is unclear, diagnosis is usually based on clinical signs including: plantar heel pain when weight‐bearing after a period on non‐weight‐bearing, pain that eases with initial activity, but then increases with further use as the day progresses, and pain on palpation [1, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following research was performed on 10 stroke patients diagnosed with plantar fasciitis, and the conditions for selecting the candidates were as follows7, 15,16,17,18 ) : patients diagnosed with hemiparalysis due to stroke who had been at the chronic stage for 6 months to 2 years but could walk on their own; patients who had been diagnosed by a rehabilitation expert as having plantar fasciitis on the paralyzed side based on an ultrasonic image diagnosis (ultrasonic image must have shown that the thickness of the plantar fascia was over 4 mm from the standard point of the calcaneus rim); patients with at least G1 plantar flexors of the ankle on the paralyzed side as, evaluated through the MAS; patients who did not have other foot injuries, tarsal tunnel syndrome, Achilles tendinitis, nerve entrapment syndrome, or any other symptoms in the foot that were causing pain; and patients who could understand the researchers commands and execute them. All subjects agreed voluntarily to participate in this research.…”
Section: Methodsmentioning
confidence: 99%
“…Stretching is frequently utilized as a conservative treatment for plantar heel pain [14,15] and systematic reviews and studies investigating the efficacy of conservative treatments for plantar fascia published different findings [16][17][18]. Di Giovanni et al found that exercise program focused on distension of the plantar fascia resulted in less pain, better patient satisfaction, and a higher functional status than exercise focusing on distension of the Achilles tendon and plantar fascia [19,20].…”
Section: Stretchingmentioning
confidence: 99%